Pengaruh Kecepatan Aliran Terhadap Gerusan pada Sekat Kanal dengan Saluran 5 Meter - Isnan Hanafi; Haiki Mart Yupi; I Made Kamiana (Jurnal Basement : Jurnal Teknik Sipil, 2023)
Canal blocking is a water-retaining structure built with the aim of reducing flow velocity and retaining air inthe canal and the surrounding area. The canal blocking to be constructed must meet stability requirementswhich are one of the important requirements to guarantee the life and main function of the canal blockingbuilding. However, so far data and information regarding effective canal blocking (having a stable structureand long service life) is still very limited. This study aims to determine the effect of airflow velocity on scourin the physical model of canal blocking. The research method used is the observation method. The researchlocation was carried out in Palangka Raya City with a research time of one month from March 25 2022 toApril 23 2022. Data analysis was carried out using graphs to determine the effect of flow velocity on scourvalues. The results showed the flow velocity used v1= 0.019 m/s and v2= 0.028 m/s greatly affected the scourvalue that occurred. The greater the velocity of the water flow used with the upstream water level of 23 cm(fixed) and the downstream water level of 6.6 cm and 23 cm along with the longer testing time, the greater thevalue of the scour depth.